2021
DOI: 10.2174/1745017902117010280
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life of People with Cancer in the Era of the COVID-19 Pandemic in India: A Systematic Review

Abstract: Background: The recent pandemic of COVID-19 caused havoc on the health system globally and raised a lot of questions and issues. Treatment for cancer is an emergency that cannot be taken back, particularly in an era of global pandemics. Cancer treatment mainly includes chemotherapy, surgery, radiotherapy, and palliative care, and because of the pandemic, all of these treatments are affected. The COVID-19 pandemic also had a potential effect on the quality of life and mental health of patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…This decrease is due to the lack of referrals from people and the fear of coronary heart disease, as well as the cancellation of meetings due to the reduction of the presence of health professionals in diagnostic centers and their obligation to be on the front line of coronation, namely, hospitals and centers (18). Treatment considering that cancer is preventable and treatable in the early stages, and on the other hand, reducing the number of people seeking screening, it is predicted that tens of thousands of deaths due to cancer progression will occur in the coming decades (5). It should be noted that not all screening delays are dangerous, and it is worthwhile for specialists in each field to provide the necessary information to the public so that people can assess the extent of cancer and coronary heart diseases and make realistic decisions during the pandemic (37,38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This decrease is due to the lack of referrals from people and the fear of coronary heart disease, as well as the cancellation of meetings due to the reduction of the presence of health professionals in diagnostic centers and their obligation to be on the front line of coronation, namely, hospitals and centers (18). Treatment considering that cancer is preventable and treatable in the early stages, and on the other hand, reducing the number of people seeking screening, it is predicted that tens of thousands of deaths due to cancer progression will occur in the coming decades (5). It should be noted that not all screening delays are dangerous, and it is worthwhile for specialists in each field to provide the necessary information to the public so that people can assess the extent of cancer and coronary heart diseases and make realistic decisions during the pandemic (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…Cancer patients are a highly vulnerable group in the current pandemic due to their immunodeficiency status because of cancer and various anti-cancer therapies. Studies indicate that cancer patients are at higher risk for more severe infections and subsequent complications (5,6). Yang et al (7) examined the effects of COVID-19 on cancer patients and found that the simultaneous incidence of cancer and COVID-19 was 6%.…”
Section: Introductionmentioning
confidence: 99%
“…The median number of studies included in the systematic reviews was 31 (interquartile range, 15.5; 49). Most reviews provided data from different countries, while only two studies focused on data from India 29 and Italy 35 exclusively. The type of study designs included across reviews varied, but most reviews included data from observational study designs of cross-sectional and retrospective nature.…”
Section: Characteristics Of the Included Systematic Reviewsmentioning
confidence: 99%
“…Particularly, the first one pointed out the difficulties in diagnosing depression in elderly with cancer [ 46 ], another one regards the risk of cancer in people suffering from severe mental illnesses [ 9 ], the last one points out the relation between cancer-related inflammation an depression [ 41 ]. One additional review regard HRQoL in people with cancer in the present era of COVID-19 pandemic [ 52 ].…”
Section: Aims and Goals Of The Thematic Issuementioning
confidence: 99%
“…Recently, due to the COVID-19 pandemic, this situation is further increased worldwide, with a significant decrease and delays in cancer treatments and screening [ 50 ], as well as in the assessments of HRQoL and the other PROs [ 51 , 52 ]. In the next years, the delay in cancer care could change the recent decline in the cancer mortality rate that has been observed since 1991 [ 53 ].…”
Section: Introductionmentioning
confidence: 99%